Mobile Augmented Reality: A Tool for Effective Tourism Interpretation in Enhancing Tourist Experience at Urban Tourism Destination - Mohd, Nur Shuhadah; Ismail, Hairul Nizam; Abdul Halim, Norhazliza (Penerbit UTM Press, 2015)
The formation of tourism experience frequently subjected to complexity of individual tourist psycho-graphical factor, which leads to vast difference in the end experience formed among the respective tourist. However, the fact that travelling is highly subjected to environmental fuzziness and the issue of geographical consciousness may interfere the emotion of tourist and influence the formation of this experience. The evolution and advancement of mobile technologies had been optimized in improving the way human interact with the surrounding environment. Within this context, mobile augmented reality (AR) technology is perceived as capable in narrowing the gap between the formation of pleasant experience and the issue of geographical consciousness, thus transform the way tourist interact with the destination. Pertaining to this situation, this conceptual paper is attempted to understand the effectiveness of mobile augmented reality in enhancing tourist travel experience on the tourism destination. In relation to this aim, this study is directed to clarify the mechanism and usability of mobile augmented reality in relation to its capability in improving tourism interpretation and to discover the influence of utilization of this technology towards tourism experience. Critical review of existing literature that relevant to the research area was done in understanding on the extensiveness of impact of mobile AR on tourist and experience formation. Findings revealed the capability of AR in merging virtual information with the real world environment through the platform of mobile device able to create a more dynamic interaction between tourist and surrounding environment.